WAYANG : A MEDIA USED BY JAVANESE TO STUDY GENETICS SINCE THE OLD TIMES - Daryono, Budi Setiadi (2013)
The origin of shadow puppets (wayang) is debatable though many sholars are of opinion that it originated in India and spread to South East Asia through Indonesia on one hand and also towards west India. Indonesia is the home of same of some of the most sophisticated form of shadow theatre, called, Wayang Kulit or Wayang Purwa. The themes revolve round the epics of the Ramayana or the Mahabarata and also legends of Indonesia, known as the Panji stories. Guritno (1984) stated that wayang had been existed in Indonesia since approximately 827/903 AD, even it had been existed since 1500 BC which was used in religious ceremonies. This means that Javanese people (Indonesian) has known about wayang for quite a long time. Moreover, wayang has physical and mental differences among the figures,for example in the shape and color of facial appearance eyes, nose, mouth, voice, character, or behavior, and trait of the figures. Those were reflected in the form of their shape and play. Based on the shape and play in the wayang, it can be seen now that indonesian has known and understood about genetics for long time ago.